Improving assessment of different flow state of aortic stenosis: implication for prognosis in patients undergoing transcatheter aortic valve replacement. (3rd October 2022) - Fusini, L; Muratori, M; Tamborini, G; Ghulam Ali, S; Gripari, P; Mantegazza, V; Roberto, M; Trabattoni, P; Agrifoglio, M; Bartorelli, A L; Pontone, G; Pepi, M
Abstract: Background: Low-flow low-gradient (LF-LG) aortic stenosis (AS) may occur with preserved or depressed left ventricular ejection fraction (EF), and both situations represent the most challenging subset of patients with AS to manage and generally have a poor prognosis with conservative therapy but a high operative mortality if treated surgically. Few and controversial data exist on the outcomes of these patients compared to normal-flow high-gradient (NF-HG) AS following transcatheter aortic valve replacement (TAVR). Purpose: This study aims to better characterize patients with different transvalvular flow-gradient patterns undergoing TAVR and to examine the prognostic value of these flow state. Methods: Overall, 1208 patients with severe symptomatic AS undergoing TAVR were categorized according to flow-gradient patterns as follow: 976 patients NF-HG (DPmean >40 mmHg), 107 paradoxical LF-LG (pLF-LG: DP mean <40 mmHg, EF >50%, and SVi <35 mL/m 2 ), and 125 classical LF-LG (DP mean <40 mmHg, EF <50%, SVi <35 mL/m 2 ). Results: TAVR was feasible in all AS subtypes. When compared with NF-HG and pLF-LG, LF-LG had a worse symptomatic status (NYHA III–IV 86% vs 62% and 67%, respectively, p<0.001), a higher prevalence of eccentric hypertrophy (Figure 1, left), a higher level of LV global afterload reflected by a higher valvuloarterial impedance and a higher pulmonary pressure (Table). Valvular function after TAVR was excellent over time with respect to aortic pressure gradient (mean and peak) and aortic valve area regardless of flow state group. While intraoperative (p=0.935) and 30-day mortality (p=0.911) did not differ significantly among the 3 groups, LF-LG had a lower overall 5-year survival (LF-LG 50%, pLF-LG 65%, NF-HG 84%, p<0.001) (Figure 1, right). LF-LG AS was associated with a hazard ratio for 5-year mortality of 2.416 (95% CI: 1.658–3.520, p<0.001). Conclusions: TAVR is an effective procedure in all patients with severe AS regardless of transvalvular flow-gradient patterns. However, special care should be given to characterized hemodynamic of AS, as patients with pLF-LG had similar survival rate than patients with NF-HG, whereas survival in LF-LG patients was 2-fold higher. Therefore, being able to identify patients less likely to improve after TAVR may help to guide treatment decision. Funding Acknowledgement: Type of funding sources: None.